Etiological Agents of Acute Meningo-Encephalitis Syndrome: Study of 75 Cases in Rajshahi Medical College Hospital
Acute meningoencephalitis syndrome (AMES) is a life threatening condition of all ages caused by different microbial agents. Etiological diagnosis is imperative for introduction of appropriate antimicrobial agents to treat the condition. This cross sectional prospective study included seventy five (75) clinically suspected patients of AMES of different age and sex groups, who were admitted at Rajshahi Medical College Hospital (RMCH) during August, 2005 to Jun e, 2006. Cerebra spinal fluid (CSF) was studied by Gram-stained smear examination, bacterial culture, latex agglutination test (LAT), cytological and biochemical tests. The serum samples were also tested for qualitative C - reactive protein (CRP